Effect of the addition of rocuronium to 2% lignocaine in peribulbar block for cataract surgery - Vishalakshi Patil; Allauddin Farooqy; Balaraju Thayappa Chaluvadi; Vinayak Rajashekhar; Ashwini Malshetty (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Peribulbar anesthesia is associated with delayed orbital akinesia compared with retrobulbar anesthesia. To test the hypothesis that rocuronium added to a mixture of local anesthetics (LAs) could improve speed of onset of akinesia in peribulbar block (PB), we designed this study. This study examined the effects of adding rocuronium 5 mg to 2% lignocaine with adrenaline to note orbital and eyelid akinesia in patients undergoing cataract surgery. Material and Methods: In a prospective, randomized, double-blind study, 100 patients were equally randomized to receive a mixture of 0.5 ml normal saline, 6 ml lidocaine 2% with adrenaline and hyaluronidase 50 IU/ml (Group I), a mixture of rocuronium 0.5 ml (5 mg), 6 ml lidocaine 2% with adrenaline and hyaluronidase 50 IU/ml (Group II). Orbital akinesia was assessed on a 0-8 score (0 = no movement, 8 = normal) at 2 min intervals for 10 min. Time to adequate anesthesia was also recorded. Results are presented as mean ± standard deviation. Results: Rocuronium group demonstrated significantly better akinesia scores than control group at 2 min intervals post-PB (significant P value obtained). No significant complications were recorded. Rocuronium added to a mixture of LA improved the quality of akinesia in PB and reduced the need for supplementary injections. Conclusion: The addition of rocuronium 5 mg to a mixture of lidocaine 2% with adrenaline and hyaluronidase 50 IU/ml shortened the onset time of peribulbar anesthesia in patients undergoing cataract surgery without causing adverse effects.